Desenvolvimento de uma infraestrutura para o estudo de desgaste erosivo e corrosão em bombas centrífugas submersas da indústria do petróleo - Barbaresco, Eduardo Braz (2011)
The lack of pressure in the oil field makes the extraction of oil much more difficult. To solve this problem many techniques can be used. One of these is the electrical submersible pumps (ESPs) which are installed in the oil field. These pumps usually have many stages that are selected according to the height to be overcome. In some oil fields, sand production leads to an efficiency reduction and may even cause the destruction of the pump due to the erosion of its parts. In this case, the pump must be replaced resulting in great economic loss. In the present work an infrastructure was developed to simulate oil field conditions which include sand production, making it possible to study the wear mechanisms in this kind of application. The flow loop is constituted of a tank for water and oil or a mixture of both, an abrasive feeder, a hydrocyclone and a measuring system for torque, pressure, temperature and flow rate. The apparatus was successfully mounted and preliminary tests were carried out.